Defending Data from SRAM-Based Attacks. - Saroiu, Stefan (Communications of the ACM, 2025)
The accompanying paper "SRAM has no chill: exploiting power domain separation to steal on-chip secrets," by Mahmod and Hicks, reveals a new class of physical memory attacks that challenge long-held assumptions about system-on-chip (SoC) security. While traditional cold boot attacks targeted DRAM's ability to retain data briefly after power loss, this work shows that SRAM can also preserve data—if its power domain is intentionally kept on during a system reboot. By attaching a voltage probe and rebooting the SoC while keeping SRAM powered, attackers can retrieve sensitive data previously thought to be safe. This finding could reshape how hardware and software systems defend against physical memory attacks, prompting new research in both areas.